The Effect Of Using Quizizz And Wordwall Media On Cognitive Learning Outcomes Of Health Materials - Naufal Izha Manggalih; Bertika Kusuma Prastiwi; Pandu Kresnapati (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
Conventional instructional methods remain inadequate for delivering health education on sensitive topics such as Sexually Transmitted Diseases (STDs), particularly in vocational high school settings where epidemiological urgency coexists with deep sociocultural barriers that inhibit open classroom discussion. This study compared the effectiveness of Quizizz and Wordwall platforms on the cognitive learning outcomes of grade XI students at SMK Negeri 1 Kersana. A quasi-experimental approach with a non-equivalent pretest-posttest group design was applied, positioning both classes as active experimental groups: Experimental Group I used Quizizz (n=36) and Experimental Group II used Wordwall (n = 33), totaling 69 students selected through purposive sampling during the Ramadan academic period. The 25-item multiple-choice instrument was validated through expert judgment, producing an Aiken's V index of 0.91 and a Cohen's Kappa reliability coefficient of 0.603 (p = 0.003), both confirming strong instrument quality. Data were analyzed using normalized N-gain scores and the Mann-Whitney U non-parametric test. Results showed that the Quizizz group achieved a mean N-Gain of 0.7556 (75.56%), categorized as high effectiveness, while the Wordwall group obtained 0.4968 (49.68%), categorized as moderate. A statistically significant difference was confirmed (p = 0.000), with an effect size coefficient r = 0.503 (large effect), indicating that the performance gap between groups reflects a substantive instructional difference rather than statistical chance. The competitive architecture of Quizizz, particularly its leaderboard system and real-time corrective feedback, produced stronger cognitive gains than the template-based exploration model of Wordwall. Quizizz is recommended as the primary instructional tool for PJOK teachers delivering reproductive health content in vocational settings, especially under conditions that restrict physical activity